2010
DOI: 10.1007/s00011-010-0295-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidative and anti-inflammatory potential of hesperidin and naringin on the rat air pouch model of inflammation

Abstract: It seems that both naringin and hesperidin are anti-inflammatory and antioxidative in nature, but hesperidin proved to be better than indomethacin and naringin because of more pronounced pharmacological actions without tissue toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 37 publications
8
84
0
Order By: Relevance
“…This finding is in agreement with the observation suggesting an increase in exudates and tissue LPO partly mediated via the increase in ROS/RNS radical production in carrageenan-injected animals [41,42]. Pretreatment with MEOg reversed the TBARs levels significantly.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with the observation suggesting an increase in exudates and tissue LPO partly mediated via the increase in ROS/RNS radical production in carrageenan-injected animals [41,42]. Pretreatment with MEOg reversed the TBARs levels significantly.…”
Section: Discussionsupporting
confidence: 93%
“…In order to run simulation of the naringin in various compositions of the cosolvent mixture, the one naringin molecule was placed in the center of a cubic box with volume of 24.24 nm 3 . The details of the chosen solvent mixtures are given in Table 9.…”
Section: View Article Onlinementioning
confidence: 99%
“…NRG is recognized by more and more people due to its comprehensive physiological and pharmacological effects, including antioxidant (Jung et al 2003, Jeon et al 2004, Rajadurai & Prince 2007, Bodas et al 2011, Jain & Parmar 2011, Mahmoud et al 2012, antihypercholesterolemic (Jung et al 2003, Kim et al 2004, Jung et al 2006, anti-inflammatory (Jung et al 2003, Bodas et al 2011, Mahmoud et al 2012, cardioprotection (Huang et al 2013, Chen et al 2014a and anti-apoptotic effects (Jagetia et al 2003, Kanno et al 2003. Furthermore, Huang et al (2013) and Chen et al (2014a,b) demonstrated that NRG inhibited the MAPK pathway (p38 MAPK, ERK1/2 and JNK) in HG-induced injuries in H9c2 cardiac cells.…”
Section: Introductionmentioning
confidence: 99%